A physico-chemical approach to the study of genipin crosslinking of biofabricated peptide hydrogels. (July 2018) - Chronopoulou, Laura; Daniele, Maddalena; Perez, Virginia; Gentili, Alessandra; Gasperi, Tecla; Lupi, Stefano; Palocci, Cleofe
Graphical abstract: Highlights: Peptide hydrogels were biosynthesized and chemically crosslinked with genipin. IR spectra shed light on the interaction of genipin with the hydrogel components. LC/MS measurements identified the crosslinked products. Abstract: Peptide-based hydrogels have been widely used for both tissue engineering approaches and therapeutic drug delivery mainly thanks to their tissue-like water content and tunable physicochemical properties. In particular, the modulation of the hydrogel chemical structure influences hydrogel properties. The most common approach for tuning hydrogel properties in terms of cell adhesion or release efficiency of entrapped compounds is chemical crosslinking. In this study Fluorenylmethyloxycarbonyl (Fmoc)-tripeptide hydrogels were synthetized in the presence of Genipin as a crosslinker using a biocatalyzed reverse hydrolysis reaction occurring between FmocPhe and Phe2 in the presence of Pseudomonas fluorescens lipase. Infrared Attenuated Total Reflection (IR-ATR), Liquid Chromatography coupled to Mass Spectrometry (LC-MS) and Scanning Electron Microscopy (SEM) investigations were used to investigate the interaction of Genipin with Fmoc-peptides as well as with their precursors. The whole instrumental platform allowed us to identify two crosslinked products that had never been reported previously and provide deeper insight into the use of natural crosslinkers for peptide hydrogel modification.